Reprogramming to pluripotency does not require transition through a primitive streak-like state. Issue 1 (December 2017) - Raab, Stefanie; Klingenstein, Moritz; Möller, Anna; Illing, Anett; Tosic, Jelena; Breunig, Markus; Kuales, Georg; Linta, Leonhard; Seufferlein, Thomas; Arnold, Sebastian; Kleger, Alexander; Liebau, Stefan
Abstract Pluripotency can be inducedin vitro from adult somatic mammalian cells by enforced expression of defined transcription factors regulating and initiating the pluripotency network. Despite the substantial advances over the last decade to improve the efficiency of direct reprogramming, exact mechanisms underlying the conversion into the pluripotent stem cell state are still vaguely understood. Several studies suggested that induced pluripotency follows reversed embryonic development. For somatic cells of mesodermal and endodermal origin that would require the transition through a Primitive streak-like state, which would necessarily require an Eomesodermin (Eomes ) expressing intermediate. We analyzed reprogramming in human and mouse cells of mesodermal as well as ectodermal origin by thorough marker gene analyses in combination with genetic reporters, conditional loss of function and stable fate-labeling for the broad primitive streak markerEomes . We unambiguously demonstrate that induced pluripotency is not dependent on a transient primitive streak-like stage and thus does not represent reversal of mesendodermal developmentin vivo .